Determinants of customers’ adoption of mobile banking in Tanzania: Further evidence from a diffusion of innovation theory - Neema Mori; Rosallia Mlambiti (Journal of Entrepreneurship, Management and Innovation)
The main goal of this study was to examine the influence of demographic factors on the adoption of innovative mobile banking services in Tanzania. It utilized Rogers’ Diffusion of Innovation Theory (DIT) to ascertain the importance of situation-based demographic factors. A survey was conducted with 416 customers of a leading bank in Tanzania. The study applied self-administered questionnaires completed by the respondents who had agreed to participate. The data were analyzed using a combination of descriptive and multivariate analyses. The descriptive results revealed that the majority of respondents used mobile banking once to three times a week to check their balance, download a mini-statement, pay different bills, transfer funds from their account to a mobile telecom network, and buy airtime. The regression results further showed a positive and significant relationship between level of income and education attainment on the one hand and the adoption of mobile banking on the other. The study argues that promotional practices and awareness-raising campaigns are needed to capture the demographic profiles of customers in order to encourage them to adopt mobile banking. Theoretically, the study has shown the relevance of applying the situation-based theory to the adoption of innovative technologies as regards banking services in Tanzania. It also broadens our understanding of the importance of demographic factors that have received little attention from the dominant socio-psychological theories.